2013
DOI: 10.1136/acupmed-2012-010254
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Alleviates Intraoperative Immunosuppression in Patients Undergoing Supratentorial Craniotomy

Abstract: Background Clinical experience suggests that anaesthesia using a combination of acupuncture and drugs can reduce the dosage of anaesthetics required for craniotomy, decreasing both the disturbance in physiological functions during the operation and postoperative complications and improving the rate of recovery. The aim of the present study was to investigate the impact of electroacupuncture (EA) on the dynamic equilibrium of the immune system and immune cell populations during the pericraniotomy period. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 20 publications
(19 reference statements)
0
28
0
Order By: Relevance
“…Many studies have indicated that postoperative pain is one of the most important factors causing immunosuppression during the perioperative period (Li et al, 2013). Rational analgesics may effectively inhibit the stress induced by pain, reduce the incidence of complications, and promote the patient's recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that postoperative pain is one of the most important factors causing immunosuppression during the perioperative period (Li et al, 2013). Rational analgesics may effectively inhibit the stress induced by pain, reduce the incidence of complications, and promote the patient's recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 5 studies29549095107 were published between 1992 and 1999; 33 studies22242527303138454752535657586768717273747778818384929397104105106110111 were published between 2000 and 2010; the remaining 56 studies1819202123262832333435363739404142434446484950515559606162636465666970757679808285868788899194969899100101102103108109 were reported from 2010 to 2015 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…2). Indications for EA included pain (32 studies)1819212426273133363740424547515256606667727682848890929697103110111, anesthesia (8 studies)46507374868994102, stroke (7 studies)2528293462105106, depression (6 studies)235359656880, obesity (4 studies)32495470, primary dysmenorrheal/menstrual pain (4 studies)619899101, substance abuse (heroin or smoking) (3 studies)6495107, osteoarthritis (2 studies)22104, migraine (2 studies)3978, nausea and vomiting (2 studies)3857, postoperative ileus (2 studies)3591, insomnia (2 studies)6381, benign prostate hyperplasia (2 studies)7987, diabetic mellitus related diseases (2 studies)83109, carpal tunnel syndrome (1 study)100, rheumatoid arthritis (1 study)93, whiplash-associated disorders (1 study)69, constipation (1 study)48, multiple sclerosis (1 study)41, tinnitus (1 study)20, auditory hallucination (1 study)30, attention deficit hyperactivity disorder (1 study)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study by Li et al [55], electroacupuncture applied during supratentorial craniotomy surgery to the points LI-4 (Hegu), TE-5 (Weiguan), BL-63 (Jinme), LR-3 (Taichong), ST-36 (Zusanli), GB-40 (Quixu), BL-10 (Tianzhu), GB-20 (Fengchi), BL-2 (Cuanzhu), and EX-HN4 (Yuyao) appears to reduce immunosuppression of humoral and cellular constituents in patients. Perioperative acupuncture has also been shown to decrease intraoperative anesthetic requirements, but outcomes illustrating clinical translation and significance are variable [56e59].…”
Section: Intraoperative Periodmentioning
confidence: 97%